Option C
The zeros of the polynomial function f(x) = x^3 - 5x^2 - 6x is x = 0 and x = -1 and x = 6
Solution:
Given that polynomial function is f(x) = x^3 - 5x^2 - 6x
We have to find the zeros of polynomial
To find zeros, equate the given polynomial function to 0. i.e f(x) = 0
![x^3 - 5x^2 - 6x = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yxjlr7mw32jm9m44myn6brou8nzxzw1n71.png)
Taking "x" as common term,
![x(x^2 - 5x - 6) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rzsclxylxghdeulo93rrwy2kxkudwtu0yq.png)
Equating each term to zero, we get
![x=0 \text { and } x^(2)-5 x-6=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/egr9ndqkir5btfltdehn9houipzs4xatpl.png)
Thus one of the zeros of function is x = 0
Now let us solve
![x^(2)-5 x-6=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/y1ms73706n48v3tx57s05ca0mfy7f2gqa9.png)
We can rewrite -5x as -6x + x
![x^2 + x - 6x - 6 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wqeiqpy3bznfjhnm9f65qswxiebb9lth2r.png)
Taking "x" as common from first two terms and -6 as common from next two terms
![x(x + 1) -6(x + 1) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fwm0o5avthry2pl1hoqchmvzdffru6318r.png)
Taking (x + 1) as common term,
(x + 1)(x - 6) = 0
x + 1 = 0 and x - 6 = 0
x = -1 and x = 6
Thus the zeros of given function is x = 0 and x = -1 and x = 6